KH. Abdul Karim Djamak: Pendiri Dan Peletak Dasar Ajaran Jam’iyyatul Islamiyah 1926-1996 - Muhammad Nur Ilham; Supian Supian (Prodi Ilmu Sejarah, Jurusan Sejarah, Seni dan Arkeologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, bekerja sama dengan Masyarakat Sejarawan Indonesia, Jambi, 2021)
In this journal discusses the journey of Islamic religious figures from Kerinci named KH. Abdul Karim Djamak in spreading the teachings of Islam according to his understanding is based on the Quran and Hadith. But with a background religious knowledge that is considered inadequate makes its teachings viewed deviate from the general or even be said to be misguided by some people. From Abdul Karim Djamak and his followers considered the allegations is a reason used to stop that study they do it because it has disturbed the scholars who are fighting for its influence there. From the results of the research obtained, the teachings taught by Abdul Karim Djamak in his studies is how to combine between the Shari'ah, ma'rifa, tarikat, and enlightenment to his students but not all of them fully understand the level so that his teachings are vulnerable to deviations among his followers. The perverted stigma that has been attached from the beginning. The study led by Abdul Karim Djamak continued until the figure founded a religious organization called Jam'iyyatul Islamiyah which is affiliated with Golkar. Various efforts are made to obtain recognition from the public, including by officially registering the organization, asks guidance to the Indonesian Ulema Council to rectify deviations, to join national figures to join the organization. All efforts are in do not successfully completely eliminate all accusations, even up to the main figure, Abdul Karim Djamak died.